Innovation dynamics and policy in the energy sector : building global energy markets, institutions, public policy, technology and culture on the Texan innovation example /: building global energy markets, institutions, public policy, technology and culture on the Texan innovation example. (2020) - Holloway, Milton L
No abstract available